Hemorrhagic pericardial effusion leading to cardiac tamponade, as presenting feature of COVID-19 in a young man: a case report - Heidari, Amir; Hashemi, S.Enssieh; Parsa mahjoob, Mohammad; Jadbabaei, Amir Nasser (Acta Biomedica Atenei Parmensis, 2020)
Background: Coronavirus disease 2019(COVID-19) is an acute respiratory illness, caused by Severe Acute Respiratory Syndrome Coronavirus2 (SARS-COV2) which quickly grew to a pandemic in late 2019 and led to substantial public health problems. Among the extrapulmonary manifestations reported, cardiovascular implications are remarkable as they can be potentially lethal. There have been rare reports of pericardial involvement, despite the pronounced cardiovascular complications including acute myocardial injury, myocarditis, arrhythmia, cardiogenic shock and venous thromboembolism. Herein, we reported a young man with cardiac tamponade as the presenting feature of COVID-19. Case summary: An otherwise healthy 28-year-old man, was admitted with pleuritic chest pain and shortness of breath and was diagnosed with COVID-19 associated cardiac tamponade. Emergency pericardiocentesis yielded large amount of hemorrhagic pericardial effusion which resulted in symptom relief. He was successfully treated with pericardiocentesis followed by anti-viral and anti-inflammatory medications and remained asymptomatic in 1-month follow-up. Conclusion: We highlight this case to mention that “hemorrhagic” cardiac tamponade can be a life-threatening complication of COVID-19, which can be treated if diagnosed early. Therefore, clinicians should be fully aware of this cardiac complication to consider in deteriorating COVID-19 patients.